On-Farm Introduction of Some Dry Season Feeding Strategies of Cattle Farmers on the Accra Plains of Ghana and The Response of Cattle to These Strategies. - Oddoye, O.K.E. (University of Ghana, 2001)
A baseline survey and three (3) experiments (one (1) on-farm and two (2) on-station) were conducted in a study to introduce some dry season feeding strategies to cattle farmers in the Accra Plains. The baseline survey was carried out in the Dangbe East and West Districts of the Accra Plains for two main reasons: (i) to ascertain the reasons why cattle farmers had not adopted dry season feeding strategies which had been known in Ghana for some time and, (ii) to find out the types of crop residues that were available in the areas and could be used for dry season feeding. A questionnaire, designed to elicit the desired information, was randomly administered to thirty (30) farmers in each District with the help of the District Veterinary Technical Officer. All cattle farmers in both areas were found to be also crop farmers producing both cash and subsistence crops. Respondents in the Dangbe East District tended to have larger farms than their counterparts in Dangbe West (6.9 ± 0.69 ha vs 4.0 ± 0.93 ha). All Cattle owners were involved in the management of their herds in the Dangbe East District. In the Dangbe West District there were a lot of absentee owners (53.3%) who left their herds in the care of hired Fulani herdsmen, and only occasionally visited the farm. In the Dangbe East District the hired herdsman was usually an indigene. Most kraals visited (Dangbe East - 83.3%; Dangbe West - 63.3%) had multiple cattle owners numbering at least three (3). All cattle, in the survey area, relied exclusively on natural communal grazing lands. Cattle farmers were aware of seasonal production differences and had also realized that the differences were due to a lack of feed and water during the dry season. There were a few instances where calves had been supplemented with dried cassava peels and wheat bran but generally no supplementation was carried out. Herdsmen grazed cattle for longer periods during the dry season and in cases of very severe drought moved the animals and their settlement, temporarily, to a new area with better grazing resource; returning to their old settlement when conditions improved. Farmers had heard about some dry season feeding strategies such as the feeding of crop residues and the use of multipurpose trees. Most farmers were, however, not using these technologies because of inadequate contact with extension staff. Maize stover was identified as the crop residue abundant in both Districts. Based on an average maize yield of 0.5 tonnes/ha it is estimated that at least 1.5 tonnes of stover will be produced by each farmer. Cassava leaves and peels, as well as leguminous browse plants such as Griffonia simpicifolia and Jasminum dichotomum were also identified as possible feed resources. The first experiment, a feeding trial, was carried out on-farm to demonstrate to farmers the effect of supplementation on parturient cows grazing natural unimproved grasslands. The experiment was in two (2) parts, which run concurrently. The first part involved supplementation of cows only, with measurements made on both cows and calves. A supplement of urea-ammoniated rice straw was available on four (4) farms with four (4) other farms serving as controls during four (4) months o f the dry season (December 1998 to March 1999). Supplemented cows lost significantly (P < 0.05) less weight (-0.23 ± 0.009 vs -0.34 ± 0.010 kg day'1) than their unsupplemented counterparts. Calves of supplemented cows showed a slightly better mean daily weight gain (though not significantly different (P < 0.05)) than calves of un-supplemented cows (0.19 ± 0.300 vs 0.16 ± 0.320 kg day'1). Mean body condition scores of cows ( supplemented - 4.7, un-supplemented - 4.3) were not significantly (P > 0.05) affected by supplementation. There was, however, a significant time X treatment interaction. In the month of February, supplemented cows (5.0) had a significantly (P < 0.05) higher body condition score compared to un-supplemented cows (4.3). In the second part of the experiment, only calves were fed the supplement. Calves on three (3) farms were fed a supplement of urea-ammoniated rice straw with calves on three (3) other farms serving as controls. Supplemented calves showed a significantly (P < 0.05) higher weight gain than the controls (0.20 ± 0.015 vs 0.13 + 0.011 kg day’1). By the end of the project farmers had learnt to prepare urea-ammoniated rice straw by themselves without supervision. The next experiment involved an on-station feeding trial, which was carried out at the Katamanso Research Station of the Animal Research Institute during the dry season from December 1999 to March 2000. The treatments used were: grazing on natural pasture only (control) (diet 1), urea-ammoniated rice straw (diet 2), untreated rice straw supplemented with Griffonia simplicifolia (diet 3) and untreated rice straw supplemented with wheatbran (diet 4). Supplements were fed to individual animals in the test groups, with the control (diet 1) receiving no supplement. There was no significant difference (P > 0.05) between diets in terms of cow and calf growth rate (kg day'1). Cows on diet 4 showed the least mean weight loss (-0.19 ± 0.058 kg day'1) followed by cows on diet 2 (-0.30 ± 0.052 kg day'1), diet 3 (-0.31 ± 0.052 kg day'1) and the control (-0.31 ± 0.056 kg day"1) in that order. Growth rate of calves (kg day'1) of cows on diet 4 proved superior to the others (0.23 ± 0.041 kg day'1), followed closely by diet 2 (0.20 ± 0.050 kg day'1), the control (0.15 ± 0,094 kg day'1) and diet 3 (0.14 ± 0.041 kg day'1). Parirt did not significantly (P > 0.05) affect cow or calf growth rate. However, cows with high parity had the lowest cow and calf growth rate (0.32 ± 0.050 kg day'1 and 0.15 ± 0.043 kg day'1) with cows of low parity having the highest cow and calf growth rates (0.22 ± 0.061 kg day'1 and 0.19 ± 0.053 kg day'1). Cow body condition score was not significantly affected by treatment. Mean cow body condition scores were 4.3, 4.7, 4.6 and 4.5 for the control diet, diets 2, 3 and 4, respectively. There was a significant effect of month of observation (P < 0.05) but no significant month X treatment interaction (P > 0.05). By the end of the experiment in March, body condition score of control cows was significantly lower (P < 0.05) than that of cows on diets 3 and 4 but not significantly different (P > 0.05) from cows on diet 2. All the supplemented diets were also not significantly different (P > 0,05) from each other. Cow body condition score was not affected significantly (P > 0.05) by parity. Cows on diet 4 had the highest daily dry matter intake (DDMI) (775.4 g day'1) and this was significantly higher (P < 0.05) than that of cows on diet 2 (460.3 g day'1) and diet 3 (319.4 g day'1). There was a significant effect of month of observation (P < 0.01) and also a significant treatment X month of observation interaction (P< 0.001). In January DDMI of diet 3 was not significantly different (P > 0.05) from DDMI of diet 2 but was significantly lower (P < 0.05) than the DDMI of diet 4). Daily dry matter intakes of diet 2 and 4 were not significantly different (P > 0.05) from each other. In Feburary, DDMI of diet 4 was significantly (P < 0.05) different from DDMI of the other two. The situation in March was similar to that in January. There was a general increase in daily dry matter intake from January to March for all treatments. Dry matter intake of untreated rice straw was significantly (P < 0.001) higher in diet 4 (361.8 g day'1) as compared to diet 3 (132.4 g day'1) in all the months. Daily dry matter intake of untreated rice straw increased in all diets from January to March. Milk yield from the various treatments were not significantly (P > 0.05) different (control - 0.64 ± 0.029 kg, diet 2 - 0.74 ± 0.027 kg, diet 3 - 0.70 ± 0.027 kg, diet 4 - 0.69 ± 0.029 kg). Parity also had no effect on milk yield (P > 0.05). The final experiment was a metabolic trial which aimed at examining changes in rumen ecology when sheep were fed either urea-ammoniated rice atraw (diet 1) or untreated rice straw supplemented with Griffonia simplicifolia (diet 2), Jasminum dichotomum (diet 3) or wheatbran (diet4). Urea-ammoniated rice straw was the diet that had been fed on-farm and the idea was to compare this with feeding untreated rice straw supplemented with a leguminous browse common in Dangbe East {Jasminum dichotomum) or West (Griffonia simplicifolia) District, as well as a common agro-industrial by-product (wheatbran). Diet significantly affected (P < 0.01) rumen pH with diets 3 and 4 being significantly lower than those for diets 1 and 2. Mean ph were 7.25, 7.21, 6.81 and 6.81 for diets 1 to 4, respectively. There was also a time X diet interaction (P < 0.01). The pH values in all diets were, however, above the cellulolysis threshold. Rumen ammonia nitrogen was neither significantly (P > 0.05) affected by diet nor was there a significant diet X time interaction (P > 0,05). The corresponding mean rumen ammonia concentrations (mg N I'1) were 178.91, 119.84, 131.64 and 223.07 for diets 1 to 4, respectively. In terms of dry matter degradability, the potentially degradable fraction (b) and the potential degradability (a+b) were significantly affected by diet (P < 0.05). Degradation of nitrogen was not significantly affected by diet (P > 0.05). The intercept (a), potentially degradable fraction (b) and time lag {TL) for neutral detergent fibre degradation, were all affected by diet (P < 0.05). Nitrogen utilisation was, however, not significantly (P > 0.05) affected by diet. Nitrogen balance (g day'1) were 3.21, 3.76, 5.09 and 4.23 for diets 1, 2, 3 and 4, respectively. It was concluded that supplementation o f untreated rice straw with appropriate supplements gave results comparable to the feeding of urea-ammoniated rice straw in terms of rumen ecology. The following conclusions can be drawn from the study: 1. The major crop residue in the survey area was maize stover. In addition cassava leaves and peels (a by-product of processing) are also available for feeding. Leguminous shrubs (Dangbe East - Jasminum dichotomum, Dangbe West - Griffonia simplicifolia) were also present. 2. The major reason for the non-adoption of known dry season feeding technology by farmers was the lack of sufficient information and in the particular case of agro-industrial by-products, the high cost. 3. Supplementation of parturient cows grazing natural unimproved pastures with urea-ammoniated rice straw significantly reduced their weight loss during the dry season. In a similar experiment it was shown that supplementation of calves with urea-ammoniated rice straw during the dry season significantly improved their body weight gain. 4. It was concluded from experiments two (2) and three (3) that the feeding of untreated rice straw with Griffonia simplicifolia, Jasminum dichotomum or wheatbran was comparable to the feeding of urea-ammoniated rice straw. 5. The feeding of urea-ammoniated rice straw, as a dry season feed supplement, is therefore recommended. Where appropriate supplements (AIBP or leguminous browse) are available and/or affordable they can also be fed with untreated rice straw as a dry season feed supplement. A similar approach can be applied to maize stover.